2021
DOI: 10.1037/apl0000853
|View full text |Cite
|
Sign up to set email alerts
|

How critical activities within COVID-19 intensive care units increase nurses’ daily occupational calling.

Abstract: During normal and predictable circumstances, employees' occupational calling (i.e., a transcendent passion to use their talent and competencies toward positive societal impact and a sense of meaningfulness derived from working in a chosen occupational domain) is observed to be relatively stable. However, with the onset of the COVID-19 pandemic, circumstances have become anything but normal and predictable, thus putting employees' sense of occupational calling to the test. In this study, we investigate the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 66 publications
(99 reference statements)
2
51
0
1
Order By: Relevance
“…13 Alarmingly, studies revealed 2% to 13% of ICU HCPs experienced thoughts of self-harm or thoughts of better off being dead, with nurses reporting a prevalence as high as 19%. 13,16 Prevalence or severity in depressive symptoms was significantly associated with ICU employment, female identification, employment as a nurse, and presence of other psychiatric comorbidities. 10,13,15 Similarly, HCPs employed in high-risk wards such as the ICU, ED and Respiratory Department were significantly more likely to suffer from depression compared to non-clinical staff, and one Polish study discovered more than 99% of frontline employees met the Patient Health Questionnaire (PHQ-9) criteria for depressive symptoms.…”
Section: Discussion Depressionmentioning
confidence: 99%
See 4 more Smart Citations
“…13 Alarmingly, studies revealed 2% to 13% of ICU HCPs experienced thoughts of self-harm or thoughts of better off being dead, with nurses reporting a prevalence as high as 19%. 13,16 Prevalence or severity in depressive symptoms was significantly associated with ICU employment, female identification, employment as a nurse, and presence of other psychiatric comorbidities. 10,13,15 Similarly, HCPs employed in high-risk wards such as the ICU, ED and Respiratory Department were significantly more likely to suffer from depression compared to non-clinical staff, and one Polish study discovered more than 99% of frontline employees met the Patient Health Questionnaire (PHQ-9) criteria for depressive symptoms.…”
Section: Discussion Depressionmentioning
confidence: 99%
“…1,7 Prevalence of related depressive symptoms in ICU HCPs was demonstrated in one Chinese study stating 59% of nurses reported decreased appetite, 55% felt fatigued, and 26% admitted to frequent crying, while a Turkish study reported 30% of HCPs felt hopelessness and despair. 12,16 In addition, two substantial European studies measured the prevalence of substance use among ICU HCPs during the pandemic. One study claimed more than one in three intensivists took sleeping pills, 10% smoked cigarettes, and 12% reported excessive alcohol intake two months into the pandemic.…”
Section: Discussion Depressionmentioning
confidence: 99%
See 3 more Smart Citations